"Religion and Mythology : A Poetics of indianité in Francis Gilbert Ponaman’s La nuit du Swami" - Shweta Deshpande (Essays in French Literature and Culture)
La nuit du Swami (2004), a collection of short stories by the Guadeloupean writer Francis Gilbert Ponaman, echoes the history of Indian migration and the resulting Indo-Caribbean identity. Drawing on the notion of indianité, I focus on some of those stories to examine the ways in which religious practices, customs and traditions brought from India through the historical kala pani crossings of indenture, are transmitted to Guadeloupe’s sociocultural landscape. I propose to examine how Indian cultural elements, and more specifically, Hindu mythology, practices and cults are transposed into French Antillean discourse. Given the extent to which ancestral heritage is adapted in a contemporary creolized setting, I subsequently analyse the place of Indo-Caribbean literary expression in French within the context of the long ongoing francophonie-littérature monde debate.